Determinants of colorectal cancer screening in Germany: a claims data analysis - Pardey, Nicolas; Kreis, Kristine; Schmidt, Torben; Stahmeyer, Jona T.; Krauth, Christian; Zeidler, Jan (Zeitschrift für Gastroenterologie, 2021)
With an incidence of 58,000 cases per year, colorectal cancer (CRC) is the third most common type of cancer in Germany. Although guaiac-based fecal occult blood tests (gFOBT) and colonoscopy are accepted strategies for CRC screening offered for individuals aged 50 or 55 onwards, utilization rates remain low.This study examines various determinants for participation in CRC screening using claims data provided by the AOK Niedersachsen and covering the years 2014 to 2016. Using multivariate logistic regression models, we analyzed sociodemographic factors (sex, age, nationality, type of employment) associated with screening behavior, including individuals who underwent colonoscopy or gFOBT. The effect of school education and professional qualification was estimated using subgroups of employees with social insurance.The analysis consisted of 620,977 insured individuals in the study population for screening colonoscopy, while the gFOBT study population contained 845,191 individuals. With increasing age, individuals were less likely to participate in CRC screening. Participation rates for screening were higher for women than men in younger age groups. However, men in higher age groups showed increased participation rates in gFOBT screening. When compared with German citizens, Turkish citizens use the colonoscopy less often and the gFOBT more often. In contrast to employees with social insurance, unemployed individuals accept the prevention services less frequently, whereas pensioners and voluntarily insured individuals exhibit increased participation rates. In terms of education and professional qualification, we estimated a significantly lower participation rate exclusively for the least educated individuals. The results help to better understand patterns of utilization and can contribute to the development of information programs for specific groups.
Keywords: Routinedaten; beeinflussende Faktoren; Prävention; Inanspruchnahme; kolorektales Karzinom